The Influence of Vocational School Graduates on Sustainable Tourism Development of Manado Bay Beach - Warouw, Felly Ferol; Ponto, Hance; Oroh, Rolly; Rotty, Viktory Nicodemus Joufree; Kembuan, Djubir (AIBPM Publisher, 2021)
The regional characteristics of Manado city show its enormous potential as a center of tourism development, especially coastal tourism. This study aims to determine the influence of vocational school graduates in Manado City to develop its sustainable tourism. We involved tourism service actors who employing vocational schools, purposively selected as the sample. For the data analysis, we used descriptive and non-parametric statistical analysis with quantitative methodology aided with the SPSS software. The findings indicate a significant influence of vocational school graduates on the development of sustainable tourism in Manado. Thus, their role should be increased by adjoining tourism-based skills accentuated on tourism sustainability.